MODERASI SANKSI PERPAJAKAN ATAS PENGARUH MORAL PAJAK DAN KESADARAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Etika Ajeng Priadi (STIE Madani Balikpapan, 2026)
This study aims to examine the influence of tax morale and tax awareness on taxpayer compliance, as well as to evaluate the role of tax sanctions as a moderating variable. The research employs a quantitative approach, with the study population consisting of individual taxpayers registered at the East Balikpapan Pratama Tax Office. The sample was selected using a purposive sampling technique, yielding a total of 100 individual taxpayer respondents. The results of the study demonstrate that tax morale and tax awareness each exert a positive influence on taxpayer compliance. Nevertheless, the findings of the moderation analysis indicate that tax sanctions do not strengthen the relationship between tax morale and taxpayer compliance, nor do they enhance the relationship between tax awareness and taxpayer compliance. Keywords: Tax Morale, Tax Awareness, Tax Sanctions, Taxpayer Compliance.